(untitled) (Research, Society and Development, 2017)
The proposal for school inclusion has led to many discussions, debates, studies and research and has raised a number of questions about how to include students with disabilities in the common classroom. Thinking about pedagogical practice and respect for student heterogeneity leads us to reflect on the curricular organization, a relevant aspect in the viability of the teaching and learning process. The purpose of this paper is to present proposals about the curriculum and its contributions to the training of different students, especially the student with Down Syndrome in the regular classroom. As for the methodological aspects, the research was carried out through a case study, through direct observations in school and non-school contexts. The study was carried in a public school in a peripheral district of the city of Natal / RN, and had as its guiding axis the curricular practices of this school in relation to school inclusion. The results point to the curricular propositions regarding the need for curricular flexibility in order to enable the participation and learning of all students. We hope with the problematization of the shared case and its relations with the theoretical framework used, contribute to the debates about the processes of schooling of students with disabilities and their intersections with / in the inclusive curricular perspective.